Superior Rectus Transposition Surgery: Safety, Efficacy, and Place in Therapy - Akbari MR; Masoomian B; Sadeghi M; Mirmohammadsadeghi A (Clinical Ophthalmology, 2022)
Mohammad Reza Akbari, Babak Masoomian, Motahhareh Sadeghi, Arash Mirmohammadsadeghi Eye Research Center, Farabi Eye Hospital, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Arash Mirmohammadsadeghi, Farabi Eye Hospital, Ghazvin Square, Tehran, Iran, Tel +989127927992, Fax +982155409095, Email a1sadeghi@yahoo.comAbstract: Abduction limitation in esotropic Duane retraction syndrome (DRS), esotropic Mobius syndrome, and sixth nerve palsy is one of the difficult-to-manage problems in strabismus surgery. The procedure of superior rectus transposition (SRT) was introduced by Johnston et al. In this procedure, the superior rectus (SR) muscle is disinserted and sutured adjacent to the insertion of lateral rectus (LR) muscle. The purpose of this review is to explore literature about efficacy and safety of SRT and its usage in strabismus surgery.Keywords: superior rectus transposition, transposition surgery, abducens nerve diseases/surgery, abducens nerve diseases/therapy